1988
DOI: 10.1111/j.1365-2044.1988.tb09068.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol anaesthesia alters somatosensory evoked cortical potentials

Abstract: This study evaluated the effects of propofol on somatosensory evoked cortical potentials in 20 ASA grade 1 or 2 patients who underwent spinal surgery. Anaesthesia consisted of propofol, dextromoramide, 50% nitrous oxide and oxygen mixture. The induction dose of propofol was 2 mg/kg and was followed by an infusion of 6 mg/kg for the first hour and 3 mg/kg subsequently. Somatosensory evoked cortical potentials were recorded on the scalp and compared to pre-operative values using Student's paired t-test. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 4 publications
0
4
1
1
Order By: Relevance
“…In addition, over the study period, there were no identified cases fulfilling the criteria for significant SSEP changes, suggesting that this form of monitoring may be less vulnerable to interference by external factors intraoperatively. This was seen in contrast to previous reports [ 11 , 12 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, over the study period, there were no identified cases fulfilling the criteria for significant SSEP changes, suggesting that this form of monitoring may be less vulnerable to interference by external factors intraoperatively. This was seen in contrast to previous reports [ 11 , 12 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that muscle MEPs are suppressed by midazolam, volatile anesthetics, and even propofol in a dose-dependent manner. 4,9,10,12,14,16,20,21,25,28,29 Since muscle MEPs are known to be sensitive to volatile anesthetics, intravenous anesthetics are preferentially used during muscle MEP monitoring. 12,25 The bispectral index (BIS) is one of several methods used to monitor the depth of anesthesia.…”
mentioning
confidence: 99%
“…4 However, tcMEP recordings are markedly affected by anaesthetics such as nitrous oxide, barbiturates and halogenated agents and also by neuromuscular blocking agents, hypothermia and variations of blood carbon dioxide. 5 6 Propofol in low doses decreases the amplitude of the early components of the SEP, 7 but its effects on MEP have not been fully investigated 5…”
mentioning
confidence: 99%